Pengaruh Penggunaan Aplikasi Geometer’s Sketchpad pada Pembelajaran Geometri - Arnasari Merdekawati Hadi; Edi Mulyadin (Program Studi Pendidikan Matematika, 2022)
Technological advances that continue to develop currently provide roles in various fields, one of which is education. Technology-based learning can be used as a learning medium, one of the technology-based learning media that can be used in learning geometry is the geometer's sketchpad application. This app is a commercial interactive geometry software program for exploring Euclidean geometry, algebra, calculus and other areas of mathematics. The purpose of this study was to determine the effect of using the Geometer's Sketchpad application on learning geometry. The research method used is quasi-experimental. The research subjects were 46 Mathematics Education students at STKIP Bima. Data analysis using t-test. Based on the results of the analysis of the independent sample t-test and calculations using the t test, it is found that tcount > ttable (3,603 > 2,015) then Ho is rejected. So it can be concluded that there is a significant effect of the Geometer Sketchpad application on geometry learning outcomes in Mathematics Education Study Program students at STKIP Bima.